1994
DOI: 10.1159/000239181
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor, Anti-Inflammatory and Analgesic Property of Embelin, a Plant Product

Abstract: Embelin, a plant-based benzoquinone derivative, has been found to exhibit significant antitumor activity in methylcholan-threne-induced fibrosarcoma in albino rats besides enhancing their survival time. The drug also has an appreciable action on pain and inflammation. The changes in DNA, RNA and protein levels in various organs in the tumor-bearing control and the drug-treated animals were also studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(121 citation statements)
references
References 5 publications
(5 reference statements)
3
118
0
Order By: Relevance
“…17 Embelin has been shown to have anti-tumor, anti-inflammatory, and analgesic properties. 30 Our study showed that embelin counteracted the glucose-related stimulatory effect on the proliferation and production of VEGF in Mü ller cells, supporting the use of embelin in the treatment of diabetic retinopathy. In fact, recent animal studies have shown that embelin has a strong antidiabetic effect in alloxan-induced diabetic rats, as evident by a reduction in fasting blood glucose levels, significant improvement in body weights, and restoration of biochemical parameters.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…17 Embelin has been shown to have anti-tumor, anti-inflammatory, and analgesic properties. 30 Our study showed that embelin counteracted the glucose-related stimulatory effect on the proliferation and production of VEGF in Mü ller cells, supporting the use of embelin in the treatment of diabetic retinopathy. In fact, recent animal studies have shown that embelin has a strong antidiabetic effect in alloxan-induced diabetic rats, as evident by a reduction in fasting blood glucose levels, significant improvement in body weights, and restoration of biochemical parameters.…”
Section: Discussionsupporting
confidence: 67%
“…The results showed 42-fold increase at 25 mM glucose and 43-fold increase at 50 mM glucose of both proteins in a dose-dependent manner, respectively (Figure 3a). This relationship was further examined by incubation of Mü ller cells with high-glucose conditions (50 mM) and various concentrations of embelin (15,30, and 60 mM) for 72 h. The results showed that the decrease of XIAP expression by embelin led to a decrease of VEGF expression (Figure 3b).…”
Section: Embelin Reversed the Proliferation And Protein Expression Almentioning
confidence: 92%
“…Prior studies of embelin and related analogues have demonstrated its antitumor effects in xenograft models. 66 In studies in mice, rats and dogs embelin was safe, but produced a reversible decrease in testosterone and infertility. 67,68 Thus, given the prior pharmacokinetic and toxicity data, embelin could be rapidly advanced into clinical trials for the treatment of solid tumors and hematologic malignancies.…”
Section: Bir 3 Inhibitorsmentioning
confidence: 99%
“…Embelin (2,5-dihydroxy-3-undecil-1,4-benzoquinone) was obtained from Oxalis erythrorhiza Gillies ex Hooker et Arnott (Oxalidaceae) 12,21 collected in the province of San Juan, Argentina, following the procedure described by Feresin et al 14 Figure 1 shows the chemical structure of embelin. Its empirical formula is C 17 H 26 O 4 , and its molecular weight is 294.39 g mol À1 .…”
Section: Experimental Procedures Materialsmentioning
confidence: 99%